COUNCIL OF EUROPE GENDER EQUALITY STANDARDS AS A NORMATIVE LEGAL BASIS FOR THE GENDER EDUCATION DEVELOPMENT IN POST-SOVIET COUNTRIES - Hryshak, Svitlana (Educological discourse, 2017)
The article deals with the Council of Europe (COE) documents that can serve to member states as the standards towards the inclusion of gender equality principles into education system as well as the legal framework for the gender education development in Post-Soviet countries. Council of Europe key gender equality standards are specified in Resolutions and Recommendations of its governing bodies (the Parliamentary Assembly, the Committee of Ministers): on balanced participation of women and men in political and public decision making; on gender mainstreaming in education; on the implementation of Recommendation CM/Rec(2007)13 by member States; on gender equality standards and mechanisms; in Declarations and Conventions adopted by the conferences and meetings of Council of Europe member States: Declaration on Equality Between Women and Men as a Fundamental Criterion of Democracy (1997); Resolution Bridging the gap between de jure and de facto equality to achieve real gender equality (2010); Declaration: Making gender equality a reality (2009); Instambul Convention (2011); in the programming and strategic documents of the COE: Transversal Programme on Gender Equality (2012); Council of Europe Gender Equality Strategy 2014–2017. Supporting to member States to implement gender equality standards in the area of education the Council of Europe focuses on promoting gender equality in education that is a prerequisite to the achievement of de facto equality between men and women in all spheres of life in society: personal, social, economic and political; on raising awareness of the persistence of gender stereotyping in education which is root causes of gender-based violence; on encouraging girls and boys to explore new roles, activities and areas; on using of non-sexist language and non-discriminatory teaching methods; on making gender mainstreaming one of the objectives of educational and career guidance. In the article it’s identified the specific sectors and the necessary measures to incorporate the gender equality standards in post-Soviet countries for the gender education development: educational policy and normative legal base of educational institutions, including higher education; teaching materials, methods and practices of teaching; educational and career guidance; researching gender issues; monitoring of gender mainstreaming in the education system.